The impact of a coach-guided personalized depression risk communication program on the risk of major depressive episode: study protocol for a randomized controlled trial - JianLi Wang; Cindy Feng; Mohammad Hajizadeh; Alain Lesage (BMC Psychiatry)
Abstract Background Depression is a highly prevalent and disabling mental health problem. Self-help has been strongly advocated for dealing with depression. Built upon the research on risk prediction modeling and risk communication, we developed a coach-guided, personalized depression risk communication tool (PDRC) for sharing information about individualized depression risk and evidence-based self-help strategies. The primary objective of this project is to evaluate the impact of the PDRC on the 12-month risk of major depressive episode (MDE) in Canadians who are at high risk of MDE. Methods This is an assessor-blinded randomized controlled trial (RCT) with two arms. We will recruit 500 males and 500 females in the communities across the country. Individuals are eligible, if they: (1) are 18 years or older, (2) have not had a depressive episode in the past two months, (3) are at high risk of MDE based on the sex-specific risk predictive algorithms for MDE (predicted risk of 6.5% + for men and of 11.2% + for women), (4) can communicate in either English or French, and (5) agree to be contacted for follow-up interviews. After screening and baseline assessment, participants will be randomized by sex into intervention and control group in a 1:1 ratio. Participants in the intervention group will receive the coach-guided PDRC. The participants are assessed at baseline, 3 and 12 months via computer assisted telephone interview system, regarding the presence of MDE, depressive and anxiety symptoms, use of self-help strategies, mental health services use and self-efficacy. Discussion The coach-guided PDRC may empower users to actively engage in self-management, leading to reduced risk of MDE. If successful, the coach-guided PDRC will lead to a novel selective prevention program that is closely aligned with the tiered mental health services model, contributing to early prevention of depression and better mental health wellbeing. Date of trial registration : 2024-10-02. Protocol version and date December 6, 2024. Version #1. Trial registration : NCT06619366.